Calcaneus Metastasis from Follicular Thyroid Carcinoma 12 Years after Total Thyroidectomy - Rahal, Mohammad Jawad H. (Case Rep Orthop, 2018)
We report the case of a sixty-eight-year-old female patient who presented for left ankle pain; X-rays and MRI showed a benign calcaneal cyst, found to be delayed distant metastasis from primary papillary thyroid carcinoma. Patient required surgical excision of the cyst. Results of histological examination showed metastatic papillary thyroid carcinoma. The patient underwent total thyroidectomy 12 years prior to presentation, with the same pathology. Postoperatively, she was treated with radioactive iodine. At 10-year follow-up post calcaneal mass excision, she was found to have a right proximal tibial mass and found to be recurrent with the same pathology. This case reports a rare condition that will be taken into consideration in bone metastasis with thyroid cancer.